Analisis Pengaruh Kualitas Layanan, Kualitas Produk dan Harga Terhadap Tingkat Kepuasan Pelanggan Salon Johnny Andrean - Yuni Yuniawati (Forum Kerjasama Pendidikan Tinggi, 2022)
The salon business is engaged in the service sector, namely providing services in body care in general, and hair in particular. The formulation of this research is How do the variables influence service quality, product quality and price partially on the level of customer satisfaction? and how the influence of service quality variables, product quality and price simultaneously on the level of customer satisfaction. This research study aims to determine the influence of service quality, product quality and price variables partially on customer satisfaction and to find out how the variables influence service quality, product quality and price simultaneously. The sample used in this study was 100 respondents with the Slovin sampling technique which was carried out by dividing the population size by 1 (one) plus the population size multiplied by the tolerance for inaccuracy raised to the power of two. The collected data were analyzed using the validity test, reliability test. To analyze the data used Likert scale analysis and multiple linear regression tests. Test the hypothesis using the calculated T test, calculated F and the coefficient of determination (R2). The results of the research partially show that service quality (x1) and price (x3) have an effect on customer satisfaction (y), while product quality (x2) has no effect on customer satisfaction (y). While simultaneously or together service quality (x1), product quality (x2) and price (x3) have a significant effect on customer satisfaction (y).